Production and antioxidant activity of electrospun polylactic acid (pla) nanofibrous mats containing naringenin (nar) for potential wound healing applications - AYAZ SEYHAN, SERAP; CESUR, SÜMEYYE; BİLĞİÇ ALKAYA, DİLEK (My University, 2024)
In tissue engineering applications, the use of natural compounds without undesired side effects is highly preferred compared to chemical drugs. Flavonoids, polyphenolic compounds distributed widely in plant-based foods, exert diverse biological effects in cultured cells and in vivo. Flavonoids exhibit anti-inflammatory, antioxidant, anti-mutagenic, anti-cancerous, antiproliferative, and proapoptotic activities, enzyme modulating activities with minimal toxicity issues. Naringenin (4′,5,7-trihydroxyflavanone) (NAR) is a flavonoid belonging to the class flavanone, predominantly found in grape fruit, bitter orange, and other citrus fruits. It has very prominent pharmacological actions like antitumor, vasoprotective, antihypertension, antiviral, and dantishockactions. As NAR can scavenge reactive oxygen species, its use in wound dressing studies is increasing. In recent years, many studies have been carried out to produce nanofibrous materials by the electrospinning method. Electrospun nanofibers have very large surface areas, controllable pore sizes, and tunable drug release profiles. Several biocompatible polymers with excellent biocompatibility and biodegradability including polylactic acid (PLA) have been widely used for the synthesis of nanofibers using the electrospun technique. In this study, nanofibers were obtained by adding NAR at different concentrations into PLA by electrospinning technique. Morphological (Scanning electron microscopy, SEM), molecular interaction (Fourier transform infrared spectroscopy, FT-IR), thermal analysis (Differential scanning calorimetry, DSC), antioxidant activity, and physical analysis were carried out after the production process. Meanwhile, the PLA nanofibers showed the largest swelling value of 220% after immersion in phosphate buffer saline (PBS) solution for 10 days. Overall, this study demonstrates that our PLA/NAR nanofiber mats are attractive candidates for wound dressing material research and application.
Keywords: Kimya; Temel Bilimler; Chemistry; Natural Sciences; Temel Bilimler (Sci); Natural Sciences (Sci); Genel Kimya; Fizik Bilimleri; General Chemistry; Physical Sciences